Behavioral model on transmitter power amplifier and IQ imbalance - Fu, Kai (2014)
This thesis is dedicated to the subject of the behavioral model of two most important analog impairments in modern wireless transmitters – in-phase/quadrature (IQ) imbalance distortion and power amplifier (PA) nonlinear memory distortion. Despite their distinct physical characteristics, and unlike conventional ways of treating them differently and separately, this thesis is to treat these two seemingly different distortions equally and model them uniformly. Specifically, the main research efforts have gone through the following two stages: In the first stage, these two distortions are treated equally while independently, and compensated using the same methodology – digital predistortion. In this stage, the main objective is to find a better behavioral model for each distortion. Then in the next stage, these two distortions are merged as one black box, and characterized by a single behavioral model. The objective of this stage is to unify the view of the two distortions, abstract it in the implementation, and save the resources by unifying and simplifying the model.